Patterns of diversity and gaps in vascular (hemi-)epiphyte flora of Southwestern Amazonia - Obermuller, Flávio A.; Freitas, Leandro; Daly, Douglas C.; Silveira, Marcos (Phytotaxa, 2014)
Vascular epiphytes are common in tropical forests and represent a considerable part of the biodiversity in Southwestern Amazonia. The aim of this study was to determine the floristic composition, patterns of species richness, and geographical distribution and knowledge gaps (collection effort) of the epiphytic vascular flora of the Brazilian State of Acre. We analyzed the database of the Flora of Acre and found a total of 331 species and 32 families of angiosperms and ferns. Almost half of the epiphytic flora of Acre (48% of species) occurs only in Northern Brazil. Of the total species, 56% are restricted to Amazonia. The distribution of the number of collections of epiphytes is concentrated in a few locations in the state and there is a positive correlation between the number of collections of epiphytes and the general index of collection density. The low and unequal sampling effort of epiphytes across the State, the high proportion of specimens identified at best to genus, and the still steep species/sampling curve indicates that the true diversity of epiphytes in Southwestern Amazonia is expressively higher than recorded thus far. This highlights the need for efforts specifically focused on documenting under-represented taxonomic groups as well as more thorough inventory of the canopy flora in this region of Amazonia.